2011
DOI: 10.1038/nprot.2011.419
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of membrane lipid order in cells and organisms

Abstract: It is now recognized that lipids and proteins in cellular membranes are not homogenously distributed. A high degree of membrane order is the biophysical hallmark of cholesterol-enriched lipid rafts, which may induce the lateral sorting of proteins within the membrane. Here we describe a quantitative fluorescence microscopy technique for imaging localized lipid environments and measuring membrane lipid order in live and fixed cells, as well as in intact tissues. The method is based on the spectral ratiometric i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
560
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 399 publications
(584 citation statements)
references
References 44 publications
20
560
0
4
Order By: Relevance
“…In particular, analysis of the fluorescence of the di-4-ANEPPDHQ probe, which exhibits an emission shift independent of local chemical composition under different lipid packing conditions (Jin et al, 2005;Demchenko et al, 2009;Dinic et al, 2011), recently enabled the imaging of plant membrane domains at the micrometer scale (Liu et al, 2009). The relevance of this approach has been confirmed by mapping membrane domains using generalized anisotropy-based images of di-4-ANEPPDHQ-stained T cell immunological synapses (Owen et al, 2010c), together with the characterization of membrane organization of nonadherent cells (such as living zebrafish embryo tissues) labeled with this dye (Owen et al, 2012a).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In particular, analysis of the fluorescence of the di-4-ANEPPDHQ probe, which exhibits an emission shift independent of local chemical composition under different lipid packing conditions (Jin et al, 2005;Demchenko et al, 2009;Dinic et al, 2011), recently enabled the imaging of plant membrane domains at the micrometer scale (Liu et al, 2009). The relevance of this approach has been confirmed by mapping membrane domains using generalized anisotropy-based images of di-4-ANEPPDHQ-stained T cell immunological synapses (Owen et al, 2010c), together with the characterization of membrane organization of nonadherent cells (such as living zebrafish embryo tissues) labeled with this dye (Owen et al, 2012a).…”
mentioning
confidence: 87%
“…4A). We used a stringent methodology previously described in the literature for noise removal from fluorescent images (Owen et al, 2012a). This analysis eliminates ROIs that exhibit a fluorescence intensity less than 7% of the highest intensity exhibited by a ROI within the analyzed membrane surface.…”
Section: Spatial Organization Of the Tobacco Cell Pm Order Levelmentioning
confidence: 99%
“…This combined effect may undoubtedly enhance the ability of PC to induce positive curvature in the mature B cell membranes. In addition, we found that the membrane level of raft-forming [21,34] disaturated (db=0) PC species almost doubled ( Figure 3C). Furthermore, docosahexaenoic acid (DHA)-containing phosphatidylethanolamine (PE), phosphatidylinositol (PI) and phosphatidylserine (PS) species were found at significantly elevated amounts in A20 relative to 38C13 cells ( Figure 3D).…”
Section: Nanotube Growth Between B Cells Depends On Their Maturation/mentioning
confidence: 71%
“…Since dynamic tension and molecular order of PM may also be critical factors in NT growth, the effect of PM hyperfluidization by polyunsaturated fatty acid (PUFA) treatment on NT formation capacity was also investigated. B cells and the connecting NTs were characterized in terms of membrane lipid packing density by imaging di-4-ANEPPHQ polarimetric probe fluorescence and analyzing the generalized polarization [20,21]. Finally, we also examined the mechanical stability of NTs and their sensitivity to environmental mechanical effects/stress.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation